Spatiotemporal patterns of cladoceran community responses to water level variation in Haixi Lake, southwest China. Issue 2 (2nd April 2020) - Wang, Dandan; Kong, Lingyang; Wang, Jiaoyuan; Huang, Linpei; Liu, Yuanyuan; Chen, Guangjie
ABSTRACT: Hydrological regulation of lakes has been increasingly practiced around the world, with significant ecological consequences. However, little is known on how lake regulation affects community organization and succession. Crustacean zooplankton play a central role in energy transfer along lake food webs because of their intermediate trophic level. Haixi Lake, a mesotrophic deep-water reservoir in southwest China, was a shallow lake by nature but underwent dam construction and reinforcement in 1957 and 1987–1990, respectively. We applied the sediment records of cladoceran remains in Haixi to uncover the spatial and temporal changes of cladoceran assemblages along a gradient of water depth by combining a spatial survey of 27 surface sediment samples with a temporal survey of a well-dated sediment core covering the last 2 centuries. Lake depth was identified to be a paramount factor in driving the temporal and spatial variation of cladoceran assemblages, which was dominated by planktonic cladocerans such as Bosmina . With increasing water levels, a significant loss of benthic cladocerans and species diversity was noted, as well as a long-term decrease in antennule lengths of bosminids. Specifically, a threshold water depth of ∼8 m was found, possibly linked to lake water thermal stability and littoral habitat coverage. Our results highlight that water level serves as a significant factor in structuring zooplankton species composition and body sizes and should be considered for sustainable water management in regulated inland waters.